2021
DOI: 10.1002/eji.202149225
|View full text |Cite
|
Sign up to set email alerts
|

C‐type lectin receptors MR and DC‐SIGN are involved in recognition of hemocyanins, shaping their immunostimulatory effects on human dendritic cells

Abstract: Hemocyanins are used as immunomodulators in clinical applications because they induce a strong Th1‐biased cell‐mediated immunity, which has beneficial effects. They are multiligand glycosylated molecules with abundant and complex mannose‐rich structures. It remains unclear whether these structures influence hemocyanin‐induced immunostimulatory processes in human APCs. We have previously shown that hemocyanin glycans from Concholepas concholepas (CCH), Fissurella latimarginata (FLH), and Megathura crenulata (KL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…A series of papers describing and characterising these cells were published in the Journal of Experimental Medicine from 1973-1975. These cells were shown to be unique potent activators of naïve T cells in comparison to other Ag presenting cell [1395,1396] and were regarded as 'accessory' cells that linked innate and adaptive immunity [1397,1398]. Human DCs traditionally include cDCs, namely CD1c + cDC2 and CLEC9A + XCR1 + CADM1 + CD141 + cDC1 and CD123 + pDCs [1399].…”
Section: Top Tricksmentioning
confidence: 99%
“…A series of papers describing and characterising these cells were published in the Journal of Experimental Medicine from 1973-1975. These cells were shown to be unique potent activators of naïve T cells in comparison to other Ag presenting cell [1395,1396] and were regarded as 'accessory' cells that linked innate and adaptive immunity [1397,1398]. Human DCs traditionally include cDCs, namely CD1c + cDC2 and CLEC9A + XCR1 + CADM1 + CD141 + cDC1 and CD123 + pDCs [1399].…”
Section: Top Tricksmentioning
confidence: 99%
“…F. latimarginata hemocyanin (FLH) was provided by Biosonda SA (Santiago, Chile). This protein was isolated and purified under sterile, pyrogen-free conditions in phosphate-buffered saline ([PBS] containing sodium phosphate 0.1 M NaCl), pH 7.2 ( 24 ), and Tris buffer for FLH containing 50 mM Tris, pH 7.4, 5 mM CaCl 2.5 mM MgCl 2 , and 0.15 mM NaCl ( 25 ). All chemicals were analytical reagent grade, and solutions were prepared with human irrigation water (Baxter Healthcare, Charlotte, NC, USA) and filtered through a 0.2 µm membrane filter (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Studies performed in our laboratory showed that FLH has antitumor effects in murine melanoma and oral cancer models ( 20 ). In addition, FLH binds to TLR4 and induces the expression and secretion of Th1-type proinflammatory cytokines ( 17 , 23 , 25 ). A remarkable characteristic of hemocyanins is their carbohydrate content, which is fundamental to their structure and immunological efficacy ( 23 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monosaccharide composition of mollusc glycans includes mannose, D-galactose, fucose, N-acetyl-D-galactosamine, and N-acetyl-glucosamine residues, of which mannose is the most abundant carbohydrate [ 13 ]. Research data have demonstrated that hemocyanin glycans act as multivalent ligands that bind with high affinities to innate immune receptors on the surface of the antigen-presenting cells (APCs), such as mannose receptors and Toll-like receptors, and triggers proinflammatory responses [ 11 , 14 , 15 ]. Hemocyanins are incorporated by APCs by both macropinocytosis and receptor-mediated endocytosis, then slowly processed, which facilitates a prolonged antigen presentation to T- or B-lymphocytes, and promotes potent cell-mediated and humoral immune responses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%